Shifting perceptions and channelling commitment in higher education communities: How to grow a Quality Culture outside the lab - Anca Greere; Catherine Riley (Universidad de Deusto, 2024)
Drawing on the data collected via a European funded project with eleven higher education partners, the article proposes a five-stage working model which can be adopted in and adapted to different institutional contexts so as to shift perceptions, strengthen engagement and channel commitment with a view to developing the desired quality culture. The project explored ways in which quality in higher education was viewed and practised by three main stakeholder groups: students, academics and quality managers, referred to as three 'quality circles'. It adopted a reflective approach to issues of quality based on grassroots discussion and cooperation between key, but in some cases disengaged, stakeholders in the quality process. The project designed, tried and tested a series of activities which demonstrated lasting impact. The analysis of the project data revealed a patterning, which, if organised sequentially, carries the potential to crystalise into an action model which may be replicated by individual higher education institutions in support of advancing towards the quality culture they might be striving for. This article highlights the building blocks of the model and explains practices which can underpin their successful implementation. Received: 3 August 2023 Accepted: 9 April 2024